Development and in vitro evaluation of κ-carrageenan based polymeric hybrid nanocomposite scaffolds for bone tissue engineering - Aslam Khan, Muhammad Umar; Raza, Mohsin Ali; Mehboob, Hassan; Abdul Kadir, Mohammed Rafiq; Abd Razak, Saiful Izwan; Shah, Saqlain A.; Iqbal, Muhammad Zahir; Amin, Rashid (RSC advances, 2020)
The excellent biocompatible and osteogenesis characteristics of porous scaffolds play a vital role in bone regeneration. In this study, we have synthesized polymeric hybrid nanocomposites via free-radical polymerization from carrageenan/acrylic-acid/graphene/hydroxyapatite. Porous hybrid nanocomposite scaffolds were fabricated through a freeze-drying method to mimic the structural and chemical composition of natural bone. Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and water contact-angle studies were carried-out for functional groups, surface morphology and hydrophilicity of the materials, followed by biodegradation and swelling analysis. The cell viability, cell culture and proliferation were evaluated against mouse pre-osteoblast ( MC3T3-E1 ) cell lines using neutral red dye assay. The cell adherence and proliferation studies were determined by SEM. Physical characterization including optimum porosity and pore size (49.75% and 0.41 × 10 3 μm 2 ), mechanical properties (compression strength 8.87 MPa and elastic modulus 442.63 MPa), swelling (70.20% at 27 °C and 77.21% at 37 °C) and biodegradation (23.8%) were performed. The results indicated CG- g -AAc-3 with a high optical density and better cell viability. Hence, CG- g -AAc-3 was found to be more efficient for bone regeneration with potential applications in fractured bone regeneration.